Effect of Contract Farming on Performance of Rice Production in Birnin Kebbi Local Government of Kebbi State - Usman, Umar; Ashafa, Muhammad Nura; Mustapha, Aminu (Kashere Journal of Politics and International Relations, 2025)
Rice farming is an important segment of agricultural activities which attracts the attention of Nigerian government and other stakeholders, but it requires adequate financing. This study examined the effect of financing options on the performance of rice farming in Birnin Kebbi, Nigeria. The population of the study was 3,251 registered rice farmers in Birnin Kebbi. A sample of 356 was arrived at using Taro Yamane formula. Primary data was collected using questionnaire from 318 respondents. The study adopted the partial least squares structural equation modelling (PLS-SEM) to analyze the effect of various financing options including; government supportive programs, bank loan, grants from international organizations and contract farming on performance of rice farming in Birnin Kebbi. The findings of the study revealed that government supportive programs and bank loan have positive and significant effect on the performance of rice farming, and contract farming has no significant effect on rice farming performance, while grant from international organizations has significant but negative effect on the performance of rice farming all in Birnin Kebbi, Nigeria. The study recommended that government's supportive programs should be expanded to cover all rice producing areas in Birnin Kebbi. The study also recommended that bank loan should be encouraged and facilitate its access to rice farmers. It also recommended that assessment of the conditions attached to international grants should be made to address the negative effect. Finally, the study recommended that contract farming agreement should be made straightforward, transparent and mutually beneficial relationships with agribusinesses in Birnin Kebbi Local government, Nigeria.